Incorporation of Different Metal Ion for Tuning Color and Enhancing Antioxidant Activity of Curcumin/Palygorskite Hybrid Materials - Li, Shue; Mu, Bin; Yan, Penji; Kang, Yuru; Wang, Qin; Wang, Aiqin (Frontiers in Chemistry, 2021)
Curcuminis one of the dietary dyes extracted from turmeric and used in the prevention and treatment of various illnesses. However, the low bioavailability and poor stability of curcumin limits its relevant applications. Therefore, different metal ions including Cu2+, Zn2+, Mg2+, Al3+or Fe3+ were incorporated to tune the color, enhance the environmental stability and antioxidant activity of curcumin in the presence of palygorskite in this study. The as-prepared samples were studied using X-ray diffraction, Fourier transform infrared spectraoscopy, X-ray photoelectron spectroscopy, zeta potential, and transmission electron microscopy. In addition, the density functional theory calculation was also performed to explore the possible interaction among metal ions, curcumin and palygorskite. It was found that the color changing and stability enhancing were ascribed to the curcumin-metal ions coordination as well as chemical interactions between curcumin-metal complex and palygorskite. Moreover, the as-prepared composites showed more excellent color, thermal stability, antioxidant activity, and fluorescence properties than that of the curcumin/palygorskite composites due to the presence of metal ions. The finding of this investigation may contribute to developing the multifunctional composites with different colors and good antioxidant activity for relevant applications based on curcumin and palygorskite.